SOCIAL ASPECTS OF FISHERMEN OF COX’S BAZAR IN BANGLADESH - Mahmud, Sayeed; Mahmudul Haq, Abu; Nahar, Nazmun (PEOPLE: International Journal of Social Sciences, 2017)
This study was performed at Somiti Para of Cox’s Bazar in order to examine the social issues of fishermen. Sites of the study and number of fishermen (146) were selected purposively. Selected fishermen were interviewed with the help of prestructurred questionnaires. About 20.55% respondents’ age were between 23-27. Among the fishermen, 52.05% were educated at primary level. The study reflects that 61.21% of the respondents had smoking habit. Most of the respondents had various diseases such as 64.38% suffered from cough and cold while 25.43% got fever. Respondents received treatment for the diseases mainly from traditional village doctors. The social status of the respondents were 23.53% lower class, 64.71% lower middle class, 5.88% upper middle class and 5.88% upper class. As the fishermen were poor socio-economic class and education level not satisfactory, special attention should be taken to improve the living condition of this community. Measures should also be taken to lessen their occupational health hazards.